Carbapenemase-Producing, Carbapenem-Resistant Acinetobacter baumannii: Summary of CDC Consultations, 2017–2019. (October 2020) - Epstein, Lauren; Shugart, Alicia; Ham, David; Vallabhaneni, Snigdha; Brooks, Richard; McAllister, Gillian; Halpin, Alison; Gilbert, Sarah; Walters, Maroya
Abstract : Background: Carbapenemase-producing carbapenem-resistant Acinetobacter baumannii (CP-CRAB) are a public health threat due to potential for widespread dissemination and limited treatment options. We describe CDC consultations for CP-CRAB to better understand transmission and identify prevention opportunities. Methods: We defined CP-CRAB as CRAB isolates with a molecular test detecting KPC, NDM, VIM, or IMP carbapenemases or a plasmid-mediated oxacillinase (OXA-23, OXA-24/40, OXA-48, OXA-58, OXA-235/237). We reviewed the CDC database of CP-CRAB consultations with health departments from January 1, 2017, through June 1, 2019. Consultations were grouped into 3 categories: multifacility clusters, single-facility clusters, and single cases. We reviewed the size, setting, environmental culturing results, and identified infection control gaps for each consultation. Results: We identified 29 consultations involving 294 patients across 19 states. Among 9 multifacility clusters, the median number of patients was 12 (range, 2–87) and the median number of facilities was 2 (range, 2–6). Among 9 single-facility clusters, the median number of patients was 5 (range, 2–50). The most common carbapenemase was OXA-23 (Table 1). Moreover, 16 consultations involved short-stay acute-care hospitals, and 6 clusters involved ICUs and/or burn units. Also, 8 consultations involved skilled nursing facilities. Environmental sampling was performed in 3 consultations; CP-CRAB was recovered from surfaces of portable, shared equipment (3 consultations), inside patient rooms (3 consultations) and nursing stations (2 consultations). Lapses in environmental cleaning and interfacility communication were common across consultations. Among 11 consultations for single CP-CRAB cases, contact screening was performed in 7 consultations and no additional CP-CRAB was identified. All 4 patients with NDM-producing CRAB reported recent international travel. Conclusions: Consultations for clusters of oxacillinase-producing CP-CRAB were most often requested in hospitals and skilled nursing facilities. Healthcare facilities and public health authorities should be vigilant for possible spread of CP-CRAB via shared equipment and the potential for CP-CRAB spread to connected healthcare facilities. Funding: None Disclosures: None